The Effect of Scrum Implementation and Agile Organization on Project Productivity Mediated by Team Experience - Irpan Setiana; Yunizar (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid evolution of the digital landscape compels information technology organizations to adopt adaptive project management approaches to remain competitive. This study examines the influence of Scrum implementation and Agile organizational culture on project productivity, with team experience as a mediating factor, in small and medium-sized information technology consulting firms in Bandung, Indonesia. The research employs a quantitative explanatory design, collecting data through questionnaires from 98 project managers and analyzing it using structural equation modeling with partial least squares. The findings reveal that Scrum implementation and Agile organizational practices significantly enhance project productivity by improving efficiency, deliverable quality, and team effectiveness. However, team experience does not mediate these relationships, indicating that Scrum and Agile frameworks exert strong direct effects. This study concludes that consistent Scrum practices and Agile culture are critical drivers of project success in Bandung’s information technology sector. These insights provide practical guidance for managers to optimize project outcomes through strategic Agile adoption, emphasizing structured processes and collaborative cultures, while highlighting the need for further exploration of team experience’s role in diverse contexts.